Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fneur.2017.00400
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond the Brain: Transcutaneous Spinal Direct Current Stimulation in Post-Stroke Aphasia

Abstract: Over the last 20 years, major advances in cognitive neuroscience have clearly shown that the language function is not restricted into the classical language areas but it involves brain regions, which had never previously considered. Indeed, recent lines of evidence have suggested that the processing of words associated to motor schemata, such as action verbs, modulates the activity of the sensorimotor cortex, which, in turn, facilitates its retrieval. To date, no studies have investigated whether the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 77 publications
1
40
0
1
Order By: Relevance
“…To the best of our knowledge, this study is Although tsDCS mechanisms of action still remain debated, a growing body of evidence suggests that tsDCS interferes with cortical, corticospinal, and spinal motor output in humans. [36][37] Since spinal stimulation modulates both alpha and gamma motor neuron activity in animals, anodal tsDCS could directly inhibit gamma system in humans. 14,38 In addition, the pre-synaptic inhibition and post-activation depression induced by tsDCS could reduce spasticity by modulating interneuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is Although tsDCS mechanisms of action still remain debated, a growing body of evidence suggests that tsDCS interferes with cortical, corticospinal, and spinal motor output in humans. [36][37] Since spinal stimulation modulates both alpha and gamma motor neuron activity in animals, anodal tsDCS could directly inhibit gamma system in humans. 14,38 In addition, the pre-synaptic inhibition and post-activation depression induced by tsDCS could reduce spasticity by modulating interneuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by electrical current modelling ( Parazzini et al , 2014 ; Fregni et al , 2015 ; Fiocchi et al , 2016 ; Kuck et al , 2017 ), preclinical ( Zaghloul, 2014 , 2016 ; Weiguo et al , 2015 ), neurophysiologic ( Cogiamanian et al , 2012 ; Priori et al , 2014 ) and neuroimaging studies ( Schweizer et al , 2017 ), a growing body of literature suggests that tsDCS can modulate activity at multiple levels of the central nervous system, including the segmental spinal cord ( Winkler et al , 2010 ; Lamy et al , 2012 ; Hubli et al , 2013 ), ascending lemniscal and nociceptive pathways ( Cogiamanian et al , 2008 ; Cogiamanian et al , 2011 ; Truini et al , 2011 ), as well as cortical regions ( Bocci et al , 2014 , 2015 a , b , c ; Marangolo et al , 2017 ; Schweizer et al , 2017 ). In addition, a recent proof-of-concept study from our group, in young and neurologically intact individuals, found that anodal tsDCS applied over the lower thoracic region (T-11) concurrently with BLTT, increased the acquisition rate and retention of backward walking speed up to 2 weeks post-training ( Awosika et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic literature review including five meta-analyses and 48 studies found some evidence in the literature that tDCS could be effective for poststroke aphasia rehabilitation at the chronic stages, but there is still a lot of variability between studies (Biou et al, 2019). The nature of the task, the stimulation site, the intensity and duration of the stimulation greatly differed from one study to the other (Baker et al, 2010;Branscheidt et al, 2018;Cherney et al, 2013;Ewa et al, 2013;Jung et al, 2011;Lee et al, 2013;Manenti et al, 2015;Marangolo et al, 2014Marangolo et al, , 2017Sebastian et al, 2016;Vestito et al, 2014;Vines et al, 2011;Wu et al, 2015;You et al, 2011). Nevertheless, there is a consensus in the existing literature on the need of combining stimulation with speech-language therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The two main naming tasks found in the literature are naming of nouns and naming of verbs. The share is larger for nouns naming because of its use when authors use standardized language evaluation batteries (Baker et al, 2010;Branscheidt et al, 2018;Campana et al, 2015;Cherney et al, 2013;Fiori et al, 2011;Flöel et al, 2011;Fridriksson et al, 2018;Galletta et al, 2015;Kang et al, 2011;Lee et al, 2011;Marangolo et al, 2013aMarangolo et al, , 2013bMarangolo et al, , 2014Marangolo et al, , 2016Marangolo et al, , 2017Marangolo et al, , 2018Meinzer et al, 2016;Monti et al, 2008;Pestalozzi et al, 2018;Polanowska et al, 2013;Sandars et al, 2017;Santos et al, 2013Santos et al, , 2017Shah-Basak et al, 2015;Spielmann et al, 2018;Vestito et al, 2014;Vines et al, 2011;Volpato et al, 2013;You et al, 2011). Furthermore, generalization has been measured in several studies: some of them assessed the transfer of competence on an untrained task (Lee et al, 2011;Marangolo et al, 2011Marangolo et al, , 2013aMarangolo et al, , 2013bMarangolo et al, , 2014Marangolo et al, , 2016Marangolo et al, , 2017Manenti et al, 2015;…”
Section: Introductionmentioning
confidence: 99%